STEM-CP (Sains, Technology, Engineering Mathematics, And Contextual Problem)-Based Biology Textbook on Food Digestion System in High School - I M Oktaviani; Sutarto Sutarto; S Hariyadi; J Prihatin; A S Budiarso (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2020)
This study aimed to develop a digestive system textbook based on STMCpE for grade XI high school. The textbook is set to be a contextual textbook with problem-solving characteristics in the